On The Sets of f-Strongly Cesaro Summable Sequences - Ibrahim, Ibrahim sulaiman; Colak, Rifat (Kyungpook Natl Univ, Dept Mathematics, 2024)
In this paper, we establish relations between the sets of strongly Cesaro summable sequences of complex numbers for modulus functions f and g satisfying various conditions. Furthermore, for some special modulus functions, we obtain relations between the sets of strongly Cesaro summable and statistically convergent sequences of complex numbers.
Keywords: Natural density; Modulus function; Statistical convergence; Strong Cesaro summability